(untitled) (Bangladesh Journal of Botany, 2025)
There was positive power function correlation between tensile strength and root diameter, and a negative power function correlation between tensile strength and root diameter after single, mild and severe cyclic loading. Cyclic load significantly increased the root tensile force and strength. Compared with single load, the tensile force increased by 22.61 and 47.61%, and the tensile strength increased by 20.38 and 43.85% after mild and severe cyclic load, respectively. The strength of the root-soil complex of Artemisia nigra were linearly positively correlated with the vertical load. The greater the depth of the burying root, the lower the soiling efficiency. The strength and cohesion of the root-soil composite under the condition of soil pore water pressure is less than that of the soil pore water. The internal friction angle are positive growth rates under different soil pore water pressure conditions. The strength characteristics of the root-soil composite increase with increasing root diameter. The shear rate has no significant effect on the strength characteristics of the root-soil composite. Bangladesh J. Bot. 54(3): 667-676, 2025 (September) Special